2013
DOI: 10.1158/1078-0432.ccr-13-0624
|View full text |Cite
|
Sign up to set email alerts
|

Loss of PTEN Expression Is Associated with Poor Prognosis in Patients with Intraductal Papillary Mucinous Neoplasms of the Pancreas

Abstract: Purpose Previously, we reported PIK3CA gene mutations in high-grade intraductal papillary mucinous neoplasms (IPMN). However, the contribution of phosphatidylinositol-3 kinase pathway (PI3K) dysregulation to pancreatic carcinogenesis is not fully understood and its prognostic value unknown. We investigated the dysregulation of the PI3K signaling pathway in IPMN and its clinical implication. Experimental Design Thirty-six IPMN specimens were examined by novel mutant-enriched methods for hot-spot mutations in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 52 publications
0
40
0
1
Order By: Relevance
“…18 Here, we found that PTEN was highly activated upon GHR silencing in both PANC-1 and HPAC cells (Figures 5e and f). Activation of PTEN in GHR silenced cells efficiently enhances apoptosis and inhibits proliferation by suppressing the active status of PI3K/AKT and its intermediates.…”
Section: Resultsmentioning
confidence: 64%
“…18 Here, we found that PTEN was highly activated upon GHR silencing in both PANC-1 and HPAC cells (Figures 5e and f). Activation of PTEN in GHR silenced cells efficiently enhances apoptosis and inhibits proliferation by suppressing the active status of PI3K/AKT and its intermediates.…”
Section: Resultsmentioning
confidence: 64%
“…Previously we have reported that members of the oncogenic PI3K signaling pathway are commonly altered at genetic or expression level in human IPMNs 29, 30 . Consistent with this finding, we found that the downstream gene PDK1 (3-phosphoinositide-dependent protein kinase-1) was up-regulated in the high-grade IPMN lesions of the AKP mice by IHC (Figure S3A and B).…”
Section: Resultsmentioning
confidence: 96%
“…The details on these human IPMN specimens can be found in our previous publication 30 . The IHC were scored independently by two pathologists (H.E.R.…”
Section: Methodsmentioning
confidence: 99%
“…Human PDAC genomic studies have revealed the presence of oncogenic mutations in components of the PI3K pathway, including activating mutations in the catalytic PI3K subunit (PIK3CA/p110α), mutations in the regulatory PI3K subunit (PIK3R1/p85α), amplification of the PI3K downstream effector AKT2, and deletion/loss of tumor suppressor PTEN, a major negative regulator of PI3K (Aguirre et al 2004;Schonleben et al 2006;Jaiswal et al 2009;Ying et al 2011;Witkiewicz et al 2015). Mutations in the PI3K pathway, including PIK3CA and AKT1, are relatively common in IPMN-associated PDAC and account for >10% of cases (Schonleben et al 2006;Garcia-Carracedo et al 2013). Interestingly, the prognosis of these IPMN patients is strongly associated with loss of PTEN expression (Garcia-Carracedo et al 2013).…”
Section: Kras Signaling Surrogates In Tumor Development and Maintenancementioning
confidence: 99%
“…Mutations in the PI3K pathway, including PIK3CA and AKT1, are relatively common in IPMN-associated PDAC and account for >10% of cases (Schonleben et al 2006;Garcia-Carracedo et al 2013). Interestingly, the prognosis of these IPMN patients is strongly associated with loss of PTEN expression (Garcia-Carracedo et al 2013). Although constitutively active Pik3ca can induce PDAC formation in a GEMM (Eser et al 2013), PIK3CA mutations in human PDAC are largely concurrent with oncogenic KRAS mutation, suggesting that PI3K activation cooperates with oncogenic KRAS during pancreatic tumor development (Witkiewicz et al 2015).…”
Section: Kras Signaling Surrogates In Tumor Development and Maintenancementioning
confidence: 99%